Migration and Young Child Nutrition: Evidence from Rural China - Ren Mu; Alan De Brauw (Institute for the Study of Labor (IZA), 2013)
The unprecedented large scale rural-to-urban migration in China has left many rural children living apart from their parents. In this study, we examine the impact of parental migration on the nutritional status of young children in rural areas. We use the interaction terms between wage growth in provincial capital cities and initial village migrant networks as instrumental variables to account for migration selection. Our results show that parental migration has no significant impact on the height of children, but it improves their weight. We provide suggestive evidence that the improvement in weight may be achieved through increased access to tap water in migrant households. Concerns about the sustainability of the impact on weight are raised in the conclusions.
Keywords: I1; J6; O1; 330; migration; children; nutrition; rural China